Prostrating in The Cloud: Faith, Identity, and the New Frontiers of Islamic Civilization - Reza Fahmi; Prima Aswirna (CV. Doki Course and Training, 2026)
Introduction: The digital transformation of religious life has propelled Islamic worship into immersive virtual environments, signaling a shift in the structural expression of Islamic civilization. This study explores the emergence of